At-line testing of chlorophenol and chloroanisole contaminants in commercial wine production. - Nicholls, C. R. (Cranfield University, 2004)
The research described in this thesis concerns the development of at-line test procedures for the detection of trace levels of chlorophenols and chloroanisoles in wine and related materials. Competitive ELISA assays were developed and optimised for pentachlorophenol and pentachloroanisole to enable the detection of chlorophenols and chloroanisoles in the range 0.1 to 100ng/ml in purified sample extracts, using antibodies supplied by the French consortium partner, Diaclone, together with synthesised conjugate materials, based on the enzyme horseradish peroxidase. The cross reactivity of the assay towards chlorophenol and chloroanisole congeners in wine was investigated and the pentachlorophenol assay was selected as the most efficient antibody to detect and quantify both chlorophenol and chloroanisole congeners. The use of synthetic receptors based on molecularly imprinting technology was also investigated for pentachlorophenol and pentachloroanisole, and a new assay format (Displacement Imprinted Polymer Analysis (DIPRA)) was established to measure chlorophenols in contaminated materials at a concentration range of 0.1 to 50 Âµg/ml, based on the displacement of a reporter molecule rebound to the synthetic receptor sites. Two alternative reporter molecules were synthesised by linking a pentachlorophenol derivative (2,3,5,6-tetrachloro-4-hydroxy phenoxy acetic acid) to the enzyme horseradish peroxidase or 7-amino-4-methylcoumarin-3-acetyl hydrazide. Alternative hyphenated sample extraction and purification methods based on solid phase extraction, steam distillation and liquid/liquid partition were evaluated to enable the ELISA and DIPRA test methods to be employed using the limited facilities of a local winery laboratory. The application of the procedures to the analysis of sample types such as wine, corks and packaging materials was undertaken to investigate the suitability of the test methods for inclusion in quality control and incident analysis protocols.